Clinical Profile and Outcome of Children with Empyema Thoracis in Tertiary Hospital - Sah, Vijay Kumar; Singh, Sandip Kumar; Yadav, Sunil Kumar; Giri, Arun; Kumar, Praveen (Birat Journal of Health Sciences, 2023)
Introduction:  Empyema thoracis (ET) is an accumulation of pus in the pleural space. It is a common condition in childhood having significant morbidity and mortality. The clinical manifestations of empyema are high grade fever with chills and rigors, cough, breathlessness, chest pain. The present study analyses the epidemiological aspects of the disease, etiological agents, clinical features and associated lesions in diagnosis of empyema and the outcome of early Video-assisted thoracoscopic surgery (VATS) on morbidity of disease in children.Objectives: To study various demographic characteristic and to evaluate various management strategies and outcome in children with empyema thoracis.Methodology: This is a prospective hospital based observational study, conducted at Nobel Medical College Teaching Hospital Biratnagar, from December 2021 to November 2022. All children in the age group of 1month to 16 years diagnosed pyogenic empyema by lights criteria during the study are included in the study. Children below 1 month of age and pleural effusion not meeting the criteria for exudative pleural effusion by Light's criteria are excluded from the study.Results: Majority of the study population are in the age group of >5 years. Males are more common than females. Most common clinical feature was fever followed by cough, chest pain and shortness of breath. Culture is positive in 68% out of which 32% is staphylococcus aureus, 20% is mycobacterium tuberculosis ,16% is streptococcus pneumonia. Duration of illness is 3weeks in 12% of the children. In 80% of the children there is unilateral involvement in the x- ray chest. In the children who are uncomplicated all of them had intercoastal chest tube drain (ICD) usage,76.4% had urokinase therapy and 5.8% had undergone thoracotomy and none of them had need for surgery. In the children with complication 87.5% had ICD usage and urokinase therapy,25% of them had undergone thoracotomy and 12.5% had need for surgery.Conclusion: Empyema thoracis is more commonly seen in the males of the group>5 years with duration of illness